The open economy : tools for policymakers in developing countries - Dornbusch, Rudiger; Helmers, F. Leslie C. H.; World Bank. (New York : Published for the World Bank, Oxford University Press, 1988)
The aspects of economic policy concerning an open economy.
Includes bibliographical references and index.
ucj 17/01/2019
Loans
Keywords: Economic policy; Developing countries